Contradiction in contemporary political life: meeting bureaucracy in Norwegian municipal government. (20th March 2017) - Abram, Simone
Abstract : Meetings are the apotheosis of contemporary bureaucratic life, containing dilemmas and contradictions that are at the heart of modernity. In particular, political and bureaucratic meetings (both state and civic) are ritual performances in which rules are enacted, ritual correctness is met with manipulative political game‐playing, and formal transparency is intertwined with relational and informational secrecy. Meetings in bureaucratic government rely on a series of legitimating motifs, including the invoking of 'conjured contexts' to link bureaucratic practices to external action. This essay shows how meetings order political and bureaucratic life, and vice versa, and explores the materiality and embodiment of meeting practices, illustrating how a dominant global model of bureaucratic meeting is elaborated locally.